2001
DOI: 10.1001/archpedi.155.10.1105
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for Pediatric Intoxication in Washington State, 1987-1997

Abstract: Background: Intoxication (or poisoning) that necessitates hospitalization remains an important source of morbidity in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
44
4
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 19 publications
26
44
4
2
Order By: Relevance
“…Thus, if a specific "rural" county effect to lower hospitalizations due to poisoning by using a PCC exists, it would be hard for this effect to be seen with such a small percentage of patients meeting this rural definition in the current study. The hospitalization discharge rates for poisoning (average of 0.54/1000 person years) seen in this study are consistent with hospitalization rates for pediatric (Ͻ18 years old) intoxications (0.45/1000 person years) seen in the State of Washington [28]. The distribution of the agents involved in the Washington study was similar to those found in this study (see Table 2) with antidepressants, salicyclates, antiallergens and antiemetics, ethanol, anticonvulsants, benzodiazepines, stimulants/amphetamines, antiasthmatics, and antibiotics representing the top ten in the Washington State study [28].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, if a specific "rural" county effect to lower hospitalizations due to poisoning by using a PCC exists, it would be hard for this effect to be seen with such a small percentage of patients meeting this rural definition in the current study. The hospitalization discharge rates for poisoning (average of 0.54/1000 person years) seen in this study are consistent with hospitalization rates for pediatric (Ͻ18 years old) intoxications (0.45/1000 person years) seen in the State of Washington [28]. The distribution of the agents involved in the Washington study was similar to those found in this study (see Table 2) with antidepressants, salicyclates, antiallergens and antiemetics, ethanol, anticonvulsants, benzodiazepines, stimulants/amphetamines, antiasthmatics, and antibiotics representing the top ten in the Washington State study [28].…”
Section: Discussionsupporting
confidence: 84%
“…The hospitalization discharge rates for poisoning (average of 0.54/1000 person years) seen in this study are consistent with hospitalization rates for pediatric (Ͻ18 years old) intoxications (0.45/1000 person years) seen in the State of Washington [28]. The distribution of the agents involved in the Washington study was similar to those found in this study (see Table 2) with antidepressants, salicyclates, antiallergens and antiemetics, ethanol, anticonvulsants, benzodiazepines, stimulants/amphetamines, antiasthmatics, and antibiotics representing the top ten in the Washington State study [28]. The call penetrance reported in the current study (average of 8.5 calls/1000 person years) is very similar to that seen in a study of rural counties (8.13-8.21 calls/1000 person years) [14].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The studies in some surrounding countries showed that the prescribed drugs represent the most common causative agent of poisoning, a pattern similar to that of the developed countries. 22 This was explainable by the change in people's life style as well as economic, and social problems existing in the society. With regard to poisoning due to drugs, sedatives take the top of the drug followed by the anti-hypertensive and analgesic medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Many household articles are dangerous in this respect and comprise the various causes of poisoning. Poisoning that necessitates hospitalization remains an important source of morbidity in children 2 . The reported incidence of childhood poisoning in various studies vary from 0.3 to 7.6% 3,4 .…”
Section: Discussionmentioning
confidence: 99%